Haematological study of caprine subclinical and clinical mastitis - Khairudin, Nurul 'Atiqah (2015)
Mastitis is an important economic disease affecting dairy farms worldwide. Haematological analysis is one of the diagnostic procedures that can provide significant information, additional to that resulting physical examination attributes. The purpose of this study is to compare the haematological parameters in three different groups of lactating does; healthy, subclinical mastitis and clinical mastitis. Blood samples were collected from 45 cross breed does; 16 healthy, 16 subclinical mastitic and 13 clinical mastitic does, from three farms of Ladang Angkat, Universiti Putra Malaysia. Blood samples were examined for different haematological parameters such as packed cell volume (PCV), haemoglobin (Hgb), and total red blood cell (RBC) count, total white blood cell (WBC) count, absolute white blood cell count as well as the mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC).The haematological parameters for all groups were compared statistically. The results revealed there was no significant difference (p>0.05) for all haematological parameters of all the groups. However, the total white blood cell counts in clinical mastitic does were significantly (p<0.05) higher than that of the healthy does, which suggest an on-going immune response during mastitis. Leukocytosis is an indicator of the inflammatory status such as acute and chronic inflammation as well as during stress. Other factors should be considered such as breeds, physiological adaptation and lactational stage that may cause variations in the haematological values. Haematological analysis should be supported by other diagnostic methods such as somatic cell count (SCC), bacteriological examination and electrical conductivity of the milk to diagnose mastitis.